Impact of Surface Undulation on Flow and Heat Transfer Characteristics in an Enclosure Filled with Nanoencapsulated Phase Change Materials (NEPCMs). (9th February 2021) - Alhashash, A.; Saleh, H.
Abstract : The present study investigates the natural convection in a wavy enclosure caused by a thermal difference between a cold wall and a hot undulated wall. The enclosure is filled with hybrid nanofluids. The hybrid nanofluids are formed of a phase change material (PCM) suspended in the water. The PCM utilizes polyurethane as the shell and nonadecane as the core. The core absorbs or releases its energy in the shape of latent heat inside the water and contributes to thermal energy storage and heat transfer. The governing equations are expressed in PDEs and solved by the finite element method (FEM). Parametric studies were used to analyze the solid concentration, fusion temperature, amplitude of corrugation, number of corrugations, and Rayleigh number. It is found that the heat transfer rate enhances by the rise of the latent heat of the NEPCM cores. The global heat transfer can be improved by more than 12 % by adding 1 % of NEPCM particles volume fraction. However, the heat transfer tends to decrease by applying the wavy surface.